IMPLEMENTASI TATA KELOLA KEUANGAN DAN SOSIAL MEDIA MARKETING PADA SEKTOR USAHA JASA MAKE UP ARTIST (MUA) HIMPUNAN AHLI RIAS PENGANTIN INDONESIA (HARPI) MELATI DI WILAYAH KECAMATAN KARANGPAWITAN KABUPATEN GARUT - Siska Marlina; Irma Rosmayati; Marissa Marissa; Asep Saefuloh (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
This community service program aims to enhance financial management skills and the utilization of social media marketing among Make Up Artist (MUA) entrepreneurs who are members of the Indonesian Bridal Makeup Artist Association (HARPI) Melati in Karangpawitan District, Garut Regency. The main issues faced by the partners include low financial literacy, mixing of personal and business finances, lack of proper financial reporting, and suboptimal marketing strategies through social media. The program was implemented through initial coordination with local authorities, socialization, lectures, workshops, bookkeeping training, social media marketing strategies, interactive discussions, and evaluations. The results indicate an improvement in participants’ ability to prepare simple financial statements, develop budget plans, and leverage social media to enhance business competitiveness. This activity is expected to support the growth of MUA businesses, increase income, and contribute to reducing unemployment rates in the area.